Application of platelet activating factor for influencing some biochemical parameters of cattle and buffalo spermatozoa - KUMAR, SUBODH; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2014)
Frozen semen straws of 12 bulls each of Karan Fries cattle and Murrah buffalo with varying conception rates were taken and after appropriate thawing, they were twice washed in sperm TALP medium. Semen was treated with 200 mM of platelet activating factor (PAF) for 15 min at 38°C and 5% CO 2 level. It was centrifuged at 1 500 rpm for 20 min to obtain the supernatant from which activities of 3 enzymes, viz. hyaluronidase (HLO), GOT and GPT were assayed. Comparison was made with controls (ie. devoid of PAF). Paired t-test revealed that PAF caused a significant (P<0.01) increase in HLO while nonsignificant (P<0.05) effect on OOT and OPT activities. The overall HLO, GOT and GPT activities for controls, treated samples, (net change) averaged 0.045 ± 0.003, 0.115 ± 0.004, (0.070);18.99 ± 1.31, 18.77 ± 1.49, (-0.22) and 17.18 ± 1.14, 17.73 ± 0.98, (0.55) units, respectively, for cattle. The corresponding values for buffalo averaged 0.045 ± 0.003,0.124 ± 0.004, (0.079); 17.62 ± 1.42, 17.78 ± 1.33, (0.16) and 13.0H 1.31, 13.76 ± 1.54, (0.73) units respectively.